Avaliação dos marcadores séricos - ácido hialurônico (AH), YKL40 e fator de crescimento e transformação 1 (TGF-1) - no diagnóstico da esquistossomose mansônica hepatoesplênica - Izabela Voieta da Silva Teixeira (2012)
Introduction: Serum biomarkers have been used as a tool in the diagnosis and evaluation of liver fibrosis intensity in hepatosplenic schistosomiasis with variable results. Few studies have used liver biopsy in the confirmation of Symmers' fibrosis and more frequently physicians rely upon imaging techniques as gold standard in the evaluation of liver fibrosis severity. Objective: Herein we evaluated the importance of hyaluronic acid (HA), YKL-40 and transforming growth factor Beta1 (TGF-1) in the diagnosis of hepatosplenic schistosomiasis and in the evaluation of liver fibrosis intensity using imaging techniques and surgical wedge liver biopsy. Methodology: Sixty patients with schistosomiasis mansoni were selected for this study. Thirty (Group 1) had hepatosplenic schistosomiasis and they were attending the Centro de Treinamento e Referência em Doenças Infecciosas e Parasitárias, UFMG (patients, in this group, had no evidence of active Schistosoma mansoni infection); 23 were male (76.7%) in the mean age of 39.2 years (±9.7). Another 30 patients had hepatointestinal schistosomiasis (Group 2) and they came from endemic areas of Minas Gerais (with viable eggs in the stool); 15 were male (50.0%), mean age of 35.5 years (±12.7). All patients were submitted to clinical examination and abdominal ultrasound; a blood sample was collected and stored for further analysis. The hepatosplenic group was submitted to other tests, such as: serology for hepatitides B and C, upper digestive endoscopy, abdominal magnetic resonance and surgical liver wedge biopsy. The serum markers of fibrosis were measured using commercial kits. For ultrasound an ALOKA SSD 1700 Dynaview apparatus was used and for magnetic resonance a GE 1.5 tesla instrument. Liver fragments obtained during surgery were fixed in 10% buffered formalin and afterwards embedded in paraffin wax. Five m (micrometers) slices were stained using Hematoxylin-Eosin and examined under light microscopy. Other fragments were stained with Picrosirius red and portal tracts were selected by the examiner and quantified by the software Image-Pro-Plus. Collected data were stored in EpiData 3.1 and the software R Project for Statistical Computing, 2.14.0 version was used for statistical analysis. Results: Both hyaluronic acid and YKL40 had no value in the diagnosis of liver fibrosis (they did not separate patients with hepatosplenic from hepatointestinal schistosomiasis) when imaging techniques were used for liver fibrosis identification. Serum levels of TGF-B1 were higher in the sera of patients with hepatointestinal schistosomiasis compared to patients with the hepatosplenic form of the disease. Intensity of liver fibrosis classified by histology did not coincide with serum levels of the biomarkers evaluated in this study. There was moderate correlation between serum levels of hyaluronic acid when it was compared to histomorphometry (p=0.006). There was a good concordance between imaging techniques and liver biopsy in the classification of liver fibrosis intensity. Conclusions: Hyaluronic acid and YKL40 were not useful as a marker of liver fibrosis in our study. TGF- 1, also, was not a good marker of liver fibrosis but its serum levels were significantly higher in patients with hepatointestinal schistosomiasis as compared to hepatosplenics. Therefore, TGF-1 may be a marker of active S. mansoni infection. The biomarkers used in the present study were not important in classifying schistosomiasis liver fibrosis severity.